Pengaruh Environmental, Social, and Governance terhadap Kinerja Keuangan - Ferdiansyah Ferdiansyah; Elsa Herliana Putri; Rian Evendi (AKUNTANSI 45, 2026)
This study aims to analyze the influence of Environmental, Social, and Governance (ESG) practices on the financial performance of companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. The research applied a quantitative approach using secondary data obtained from annual and sustainability reports, with purposive sampling techniques resulting in 40 observations. Financial performance was measured using Return on Assets (ROA) as the main proxy, while ESG performance was evaluated based on the Global Reporting Initiative (GRI) index. The data were analyzed using panel data regression with the Random Effect Model (REM) to determine the relationship between ESG dimensions and company financial performance. The results indicate that the Environmental dimension has a positive and significant effect on financial performance, showing that companies with stronger environmental responsibility and sustainability practices are more likely to achieve higher profitability and operational efficiency. Meanwhile, the Social and Governance dimensions were found to have no significant impact on financial performance. These findings suggest that environmental commitment has become an important factor in improving corporate financial outcomes and strengthening long-term business sustainability in publicly listed companies.